Konseptualisasi Etika Profesi Pegawai Bank - Marsa Mahendra; Siti Asyiah; Putri Saraswati; Surya Sukti (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
The profession of bank employees is an honorable one and carries great responsibility in maintaining the stability of the financial system and public trust. In carrying out their duties, bank employees are subject to legal protections and strict banking codes of ethics. However, in reality, violations of the code of ethics do sometimes occur, caused by various factors ranging from weak internal supervision to a lack of understanding of professional ethics itself. Therefore, this research aims to examine in depth the conceptualization of professional ethics for bank employees. The research method used is library research and internet searching. Data collection techniques were carried out by reviewing various sources of information, such as legal books, scientific journals, legislation, and other credible sources relevant to the issues studied. The results of the study indicate that the code of ethics for bank employees is a set of moral principles that serves as the foundation of personal integrity and professional behavior.